Економічна безпека України : поняття, структура та проблема забезпечення - Яковенко, Р. В.; Yakovenko, R.; Сігова, Х. В.; Sihova, H. (Ексклюзив-систем, 2017)
Розкрито різні підходи до поняття „економічна безпека країни”, визначено головні критерії її оцінки. Запропоновано заходи щодо її зміцнення. Different approaches to the concept „economic security of the country” are revealed, the main criteria of its estimation are determined. Measures to strengthen it are proposed.
Economic security of Ukraine : concept, structure and problem of provision
Keywords: дестабілізуючі фактори; економічна безпека країни; ризики; політична ситуація; тінізація економіки; destabilizing factors; economic security of the country; risks; political situation; shadowing of the economy